Genome-wide identification and comprehensive analysis reveal potential roles of long non-coding RNAs in fruit development of southern highbush blueberry (Vaccinium corymbosum L.) - Li, Shuigen; Zhang, Jiaying; Zhang, Liqing; Fang, Xianping; Luo, Jun; An, Haishan; Zhang, Xueying (Frontiers in Plant Science, 2022)
Blueberries have a high antioxidant content and are produced as healthy food worldwide. Long non-coding RNAs (lncRNAs) are a type of regulatory RNAs that play a variety of roles in plants. Nonetheless, information on lncRNAs and their functions during blueberry fruit development is scarce in public databases. In the present study, we performed genome-wide identification of lncRNAs in a southern highbush blueberry using strand-specific RNA-Seq. Differentially expressed lncRNAs (DE-lncRNAs) and their potential target genes were analyzed at four stages of fruit development. These findings included a total of 25,036 lncRNAs from 17,801 loci. Blueberry lncRNAs had shorter transcript lengths, smaller ORF sizes, fewer exons, and fewer isoforms than protein-coding RNAs, as well as lower expression levels and higher stage-specificity during fruit development. A total of 105 DE-lncRNAs were identified among the comparison group of PAD vs. CUP, 443 DE-lncRNAs were detected when comparing CUP with PINK fruits, and 285 DE-lncRNAs were revealed when comparing PINK and BLUE fruits. According to Kyoto Encyclopedia of Genes and Genomes annotation, cis-target genes of DE-lncRNA were primarily enriched in the ‘Autophagy-other’ and ‘DNA replication’ pathways during the early fruit developmental stages. In contrast, during the maturation stage, cis-target genes were enriched in ‘Endocytosis’ and ‘Brassinosteroid biosynthesis’. Cis-regulatory DE-lncRNAs were predicted using co-localization analysis, and their potential functions may be related to fruit expansion and ripening. Moreover, several lncRNAs have been proposed as cis-regulators of the key genes involved in flavonoid biosynthesis. MSTRG.107242.6, and its putative target gene, BTB/POZ and TAZ domain-containing protein, might play critical roles in anthocyanin accumulation in blueberries. These findings highlight the regulatory function of lncRNAs and aid in elucidating the molecular mechanism underlying blueberry fruit growth.